Timing of Radiotherapy after Radical Prostatectomy: Effects on Health-Related Quality of Life. Issue 5 (29th November 2021) - Westhofen, Thilo; Buchner, Alexander; Schlenker, Boris; Becker, Armin; Li, Minglun; Belka, Claus; Stief, Christian G.; Schmidt-Hegemann, Nina-Sophie; Kretschmer, Alexander
Abstract : Purpose: The optimal timing of radiotherapy (RT) after radical prostatectomy (RP) remains controversial with unknown impact on health-related quality of life (HRQOL). We aimed to compare the influence of early RT (eRT) and deferred RT (dRT) on HRQOL. Materials and Methods: A total of 4, 511 patients were analyzed. Inclusion criteria encompassed: ≥pT3, International Society of Urological Pathology grade ≥4, or positive surgical margin. A 1:4 propensity score-matched-analysis of 1, 599 patients was conducted (307: eRT, ≤6 months after RP; 1, 292: dRT, >6 months after RP). Primary end point was general HRQOL (based on European Organisation for Research and Treatment of Cancer QLQ-C30). Pearson correlation and binary logistic regression models were used to estimate the impact of timing of RT on HRQOL. Functional outcome was assessed using the International Consultation on Incontinence Questionnaire, short form (ICIQ-SF) and International Index of Erectile Function (IIEF-5) questionnaires. Results: Median followup was 38 months. At 12 months and 24 months followup, general HRQOL scores were significantly higher for dRT (52.7 vs 35.5; p=0.001; 45.8 vs 37.3; p=0.026). ICIQ-SF scores were higher (8.5 vs 6.1; p=0.001; 8.4 vs 7.3; p=0.038), and IIEF-5 scores were lower (1.8 vs 4.2; p=0.001; 2.2 vs 4.4; p=0.005) for eRT at 12 months and 24 months. On multivariate-analysis, dRT was associated with superior general HRQOL at 12 months (OR 0.59, 95% CI 0.37–0.94, p=0.027) and 24 months (OR 0.64, 95% CI 0.39–0.99, p=0.043), respectively. A longer time interval between RP and RT was associated with improved general HRQOL (OR 1.09, 95% CI 1.038–1.143; p <0.001). Conclusions: dRT yields improved short-term HRQOL compared to eRT. Since longer time intervals between RP and RT predict better short-term HRQOL, our data provide further support for the concept of deferred RT at low prostate specific antigen recurrence.